A aplicação do GNSS na medição do comportamento estático e dinâmico de grandes estruturas de engenharia civil e de fenómenos geofísicos - Lima, J. N. (2013)
The GNSS is being currently applied to measure static and dynamic response of large civil engineering structures and geophysical phenomena. The GNSS in static mode is more suitable for long-term monitoring because this positioning method is characterised to detect low frequency displacements with millimetric level accuracy. Of course, on short-term monitoring it is required the GNSS in more expeditious mode, like Real Time Kinematic (RTK) or Post Process Kinematic (PPK). However, it is well known that multipath effects and low sampling rates affect the accuracy of high frequency GNSS displacement measurements. In order to assess the accuracy of GNSS in kinematic mode, a test on a three-storey building scale model was carried out, where a modal identification obtained by GNSS in PPK mode is compared with an analytical model. In this paper the test is described in detail, the results obtained are analysed and a conclusion is drawn in order to apply the GNSS for large civil engineering structures and geophysical phenomena monitoring.